EEG-based local brain activity feedback training—tomographic neurofeedback - Bauer, Herbert; Pllana, Avni (Frontiers in Human Neuroscience, 2014)
Along with the development of distributed EEG source modeling methods, basic approaches to local brain activity (LBA-) neurofeedback have been suggested. Meanwhile several attempts using LORETA and sLORETA have been published. This article specifically reports on ‘EEG-based Local Brain Activity (LBA-) feedback training’ developed by Bauer et al (2011). LBA-feedback has the advantage over other sLORETA-based approaches in the way that feedback is exclusively controlled by EEG-generating sources within a selected cortical region of training (ROT): feedback is suspended if there is no source. In this way the influence of sources in the vicinity of the ROT is excluded. First applications have yielded promising results: aiming to enhance activity in left hemispheric linguistic areas, 5 experimental subjects increased significantly the feedback rate whereas 5 controls receiving sham feedback did not, both after 13 training runs (U-test, p < 0.01). Preliminary results of another study that aims to document effects of LBA-feedback training of the ACC and DLPFC by fMRI revealed more local ACC-activity after successful training (Radke et al., 2014).